Approaching a collaborative research agenda for health systems performance in circumpolar regions - Chatwood, Susan; Bytautas, Jessica; Darychuk, Anthea; Bjerregaard, Peter; Brown, Adalsteinn; Cole, Donald; Hu, Howard; Jong, Micheal; King, Malcolm; Kvernmo, Siv; Veillard, Jeremy (International Journal of Circumpolar Health, 2013)
Health care in Canada's north and circumpolar regions faces considerable challenges with the remote and widely dispersed population, harsh environmental conditions, and human resource challenges. Despite per capita expenditures that are among the highest in the world, health outcomes continue to lag behind the rest of Canada, and health disparities between the Indigenous and non-Indigenous populations within the north persist. While improving the health of northerners requires addressing underlying social determinants, transforming the health care system holds promise for health improvements in the short- and medium-term . The evidence required to inform a northern-focused and relevant transformation of health care systems remains to be generated and applied. This seminar set out to identify priority areas for a research initiative that will address systems challenges and engage decision-makers in these jurisdictions. The overarching objectives of the seminar were to explore the priority areas for health systems research in circumpolar regions, and to propose how we might best maximize our current resources, and facilitate partnerships for the advancement of a common agenda.